CdS-ZnSe heterojunction photocatalytic material with high exposure ratio of {002} active crystal face as well as preparation method and application of CdS-ZnSe heterojunction photocatalytic material
By synthesizing Cu7S4 nanosheets and CdS nanosheet seed crystals, and using thermal injection method to prepare CdS-ZnSe heterojunction, a 2D core-coronal structure was specially designed to improve the exposure ratio of the {002} active crystal surface, solving the problem of poor photocatalytic performance caused by insufficient exposure of the active crystal surface in the prior art, and achieving efficient photocatalytic decomposition of water-made H2.
Patent Information
- Application Number
- CN202411484969.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-07
AI Technical Summary
In the existing Group II-VI semiconductor nanoheterojunction, insufficient exposure of the active crystal surface leads to poor photocatalytic performance, and during the heterozygous combination, components tend to grow on low surface energy crystal surfaces, resulting in structural instability.
By preparing Cu7S4 nanosheets and CdS nanosheet seed crystals, and synthesizing CdS-ZnSe heterojunctions by thermal injection method, a 2D core-coronal structure was specially designed to improve the exposure ratio of the {002} active crystal surface.
The high-efficiency photocatalytic decomposition of CdS-ZnSe heterojunction was achieved to make H2 by water, with a hydrogen production rate of 17.1 mmol·g-1·h-1, which was significantly higher than the single component CdS nanosheets and ZnSe nanoparticles, and good cycle stability was maintained.
Smart Images

Figure CN119565641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and more specifically to a CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of {002} active crystal planes, a preparation method and an application thereof. Background Art
[0002] In recent years, in order to alleviate the energy crisis and environmental pollution problems, photocatalytic technology for converting solar energy into chemical energy has been widely studied. II-VI semiconductor nanomaterials have adjustable band structures and electron transport properties and have been widely used in various photocatalytic reactions, such as water decomposition to produce H 2 , CO 2 Reduction and pollutant degradation, etc.
[0003] At present, photocatalysts based on II-VI groups have developed from single components to multi-component nano-heterojunctions. By exerting the synergistic effect between different components, it is not only possible to expand the absorption range of sunlight, but also to reduce the electron-hole recombination efficiency by utilizing the modulation effect of the surface interface on carriers. However, due to the differences in the surface states of different crystal planes of each component in the heterojunction, some crystal planes cannot provide carrier transmission channels, which greatly affects the performance of the catalyst. The level of crystal surface activity is closely related to the phase structure of the material and the surface state of the crystal plane. Studies have shown that the photocatalytic performance of II-VI semiconductor nanomaterials with hexagonal wurtzite crystal phase is often better than that of cubic zinc blende crystal phase. Moreover, with the increase of the exposure ratio of the {002} crystal plane in the hexagonal crystal phase, that is, the more metal atoms with low coordination numbers on the surface account for, the higher the surface energy, and the higher the photocatalytic H production. 2 , carbon dioxide reduction, antibiotic degradation and other aspects. However, with the increase of the exposure ratio of the {002} crystal plane, the surface energy of the nanocrystals will continue to increase. In the synthesis of heterojunctions, the components usually grow anisotropically in the direction of decreasing surface energy, forming 0D nanoparticles or 1D nanorods [J. Phys. Chem. C 2015, 119,20555−20560; J. Phys. Chem. Lett., 2018, 9, 2212−2217; Chem. Mater., 2022, 34,4577−4586; J. Phys. Chem. C 2018, 122, 12158−12167], thereby reducing the surface energy of the material and maintaining the stability of the structure, but this is not conducive to the improvement of photocatalytic performance.
[0004] Therefore, synthesizing nanoheterojunctions with high exposure ratio of active crystal faces is one of the important measures to improve their photocatalytic performance. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a method for preparing a CdS-ZnSe photocatalyst with a high exposure ratio of the {002} active crystal plane and its application, so as to improve the photocatalytic performance of such heterojunction.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a CdS-ZnSe photocatalyst with a high exposure ratio of a {002} active crystal plane comprises the following steps: (1) Cu 7 S 4 Preparation of nanosheets CuCl 2 and oleylamine were placed in a three-necked flask, dehydrated and deoxygenated, and then heated until the solution was clear and light yellow, and NH 4 The oleylamine solution of SCN is reacted at a certain temperature. After the reaction is completed, it is naturally cooled to room temperature and the product is separated by centrifugation.
[0007] (2) Preparation of CdS nanosheet seeds Place CdO, oleic acid, and 1-octadecene into a three-necked flask, dehydrate and deoxygenate, and then heat to react until the solution is clear. 7 S 4 The nanosheets are evenly dispersed in the trioctylphosphine solution. Then the reaction system is cooled and the Cu 7 S 4 The trioctylphosphine solution is injected into the reaction system and reacted at a certain temperature. After the reaction is completed, it is cooled to room temperature and the product is separated by centrifugation.
[0008] (3) Preparation of CdS-ZnSe heterojunction ZnO, oleic acid and 1-octadecene are added to a three-necked flask, dehydrated and deoxygenated, and then heated to react until the solution is clear. During this period, the CdS nanosheet seeds and diphenyl diselenide obtained in the second step are evenly dispersed in oleylamine. Then the reaction system is cooled, and the prepared oleylamine solution is injected into the reaction system, maintained at a certain temperature for reaction, cooled to room temperature after the reaction is completed, and the product is separated by centrifugation.
[0009] Furthermore, in the above step (1), the CuCl 2 With NH 4 The molar ratio of SCN is 0.9-1.1 mmol:0.45-0.55 mmol, the volume of oleylamine dissolved in CuCl is 8-10 mL; the volume of NH 4The volume of the SCN oleylamine solution is 2-2.5 mL; the time for the dehydration and deoxygenation treatment is 10-15 min; the injection temperature is 195-205 ° C, the reaction temperature is 190-195 ° C, and the reaction time is 20-25 min; the speed of the centrifugal separation is 5000-6000 rpm, and the time is 2-3 min.
[0010] Furthermore, in the above step (2), the mass of CdO is 2-3 mmol, the volume of oleic acid is 4-6 mL, and the volume of 1-octadecene is 4-6 mL; the time of the dehydration and deoxygenation treatment is 10-15 min; the Cu 7 S 4 The mass of the nanosheet is 0.12-0.15 mmol, and the trioctylphosphine is 2-2.5 mL; the injection temperature is 180-190°C, the reaction temperature is 160-180°C, and the reaction time is 10-12 min; the centrifugal separation speed is 8000-9000 rpm, and the time is 3-5 min.
[0011] Furthermore, in the above step (3), the molar ratio of ZnO to diphenyl diselenide is 0.2-0.25 mmol:0.1-0.125 mmol, the volume of oleic acid is 1.2-1.5 mL, and the volume of 1-octadecene is 8-9 mL; the time for the dehydration and deoxygenation treatment is 15-20 min; the mass of the CdS nanosheet seed crystal is 0.15-0.2 mmol; the mass of the oleylamine is 1.2-1.5 mL; the injection temperature is 250-260°C, the reaction temperature is 260-270°C, and the reaction time is 20-25 min; the speed of the centrifugal separation is 8000-9000 rpm, and the time is 3-5 min.
[0012] The present invention also provides a method for preparing ZnSe particles: ZnO, oleic acid and 1-octadecene are added into a three-necked flask, dehydrated and deoxidized, and then heated to react until the solution is clear. During the reaction, diphenyl diselenide is evenly dispersed in oleylamine. Then the reaction system is cooled, and the prepared oleylamine solution is injected into the reaction system, and the reaction is maintained at a certain temperature, and after the reaction is completed, the reaction is cooled to room temperature, and the product is separated by centrifugation. The molar ratio of ZnO to diphenyl diselenide is 0.2-0.25 mmol:0.1-0.125 mmol, the volume of oleic acid is 1.2-1.5 mL, and the volume of 1-octadecene is 7-8 mL; the time for the dehydration and deoxygenation treatment is 15-20 min; the amount of oleylamine is 1.2-1.5 mL; the injection temperature is 250-260°C, the reaction temperature is 260-270°C, and the reaction time is 20-25 min; the speed of the centrifugal separation is 8000-9000 rpm, and the time is 3-5 min.
[0013] The present invention also claims a CdS-ZnSe heterojunction photocatalyst prepared by the above preparation method for photocatalytic water decomposition to produce H 2 application.
[0014] Furthermore, the above-mentioned photocatalytic reaction relies on the Labsolar-6A photocatalytic system, which has temperature and pressure sensors to monitor the temperature and pressure of the reaction in real time. The system can also be used in conjunction with a gas chromatograph to achieve automatic sampling of gas products and conduct qualitative and quantitative analysis. The system also has a magnetic stirring function, which can be used in photocatalytic water decomposition to produce H 2 This allows water to fully contact the catalyst.
[0015] Compared with the existing heterojunction of the same type, the beneficial effects of the present invention are as follows: First, the CdS-ZnSe heterojunction prepared in the present invention is a 2D core-crown structure. The characteristic of this structure is that the shorter diffusion path in the axial direction of the 2D configuration can accelerate the dissociation of excitons and the transfer of free charges. Secondly, compared with the core@shell structure, each component in the core-crown structure is exposed to the reaction system, which not only provides relatively more active sites for the photocatalytic reaction, but also allows the design of corresponding half-reactions (oxidation reactions or reduction reactions) or even full reactions according to actual needs. In a single half-reaction, the photogenerated electrons or holes can be better released into the system to react with the sacrificial agent, thereby maintaining the catalyst at a high activity level for a long time. Moreover, the CdS-ZnSe heterojunction prepared by the present invention can photocatalytically decompose water to produce H without any co-catalyst. 2 Rate up to 17.1 mmol·g -1 ·h -1Compared with single-component CdS nanosheet seeds and ZnSe nanoparticles, the hydrogen production rate of CdS-ZnSe is greatly improved ( Figure 6 a). BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 The Cu prepared in Example 1 7 S 4 TEM image of nanosheets; Figure 2 (a) TEM image, (b) X-ray diffraction image, (c) and (d) high-resolution TEM images of the CdS nanosheets prepared in Example 1; Figure 3 TEM image of the ZnSe particles prepared in Example 1; Figure 4 TEM image of the CdS-ZnSe heterojunction prepared in Example 1; Figure 5 This is the EDS element distribution diagram of the CdS-ZnSe heterojunction prepared in Example 1; Figure 6 (a) CdS, ZnSe, and CdS-ZnSe heterojunction photocatalytic water decomposition to produce H prepared in Example 1 2 Performance diagram of (b) CdS-ZnSe heterojunction photocatalytic water splitting to produce H 2 Cycle performance curve diagram. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this patent.
[0019] Example 1 A method for preparing a CdS-ZnSe photocatalyst with a high exposure ratio of a {002} active crystal plane comprises the following steps: 1. Cu 7 S 4 Preparation of nanosheets 1 mmol CuCl2 8 mL of oleylamine were added to a three-necked flask, heated to 100 °C, dehydrated and deoxygenated for 15 min, and then heated to 200 °C and maintained until the solution was clear and light yellow. During this period, 0.5 mmol of NH 4 SCN was dissolved in 2 mL of oleylamine, and then the above solution was injected into a three-necked flask and reacted at 185°C for 25 minutes. After the reaction was completed, it was naturally cooled to room temperature and centrifuged at 5000 rpm for 3 minutes.
[0020] 2. Preparation of CdS Nanosheet Seeds 2 mmol of CdO, 4 mL of oleic acid, and 6 mL of 1-octadecene were added to a three-necked flask, heated to 100°C, and dehydrated and deoxygenated for 15 min, then heated to 230°C and maintained until CdO was completely dissolved. 7 S 4 The nanosheets were evenly dispersed in 2 mL of trioctylphosphine solution. Then the reaction system was cooled to 180 °C and Cu 7 S 4 The trioctylphosphine solution was injected into the reaction system at this temperature, and then reacted at 160°C for 12 minutes. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000 rpm for 3 minutes.
[0021] 3. Preparation of CdS-ZnSe heterojunction 0.2 mmol of ZnO, 1.5 mL of oleic acid, and 7 mL of 1-octadecene were added to a three-necked flask, heated to 100 °C, dehydrated and deoxygenated for 15 min, and then heated to 280 °C and maintained until ZnO was completely dissolved. During this period, 0.15 mmol of CdS nanosheets and 0.1 mmol of diphenyl diselenide were evenly dispersed in 1.5 mL of oleylamine. Then the reaction system was cooled to 250 °C, and the prepared oleylamine solution was injected into the reaction system, then heated to 270 °C for 25 min, cooled to room temperature after the reaction was completed, and centrifuged at 8000 rpm for 3 minutes.
[0022] Preparation of ZnSe particles: 0.2 mmol of ZnO, 1 mL of oleic acid, and 7 mL of 1-octadecene were added to a three-necked flask, heated to 100 °C, dehydrated and deoxygenated for 15 min, and then heated to 280 °C and maintained until ZnO was completely dissolved. During this period, 0.1 mmol of diphenyl diselenide was evenly dispersed in 1 mL of oleylamine. Then the reaction system was cooled to 250 °C, and the prepared oleylamine solution was injected into the reaction system, then heated to 270 °C for 25 min, cooled to room temperature after the reaction was completed, and centrifuged at 8000 rpm for 3 minutes.
[0023] Example 1 Cu 7 S 4 TEM images of nanosheets, such as Figure 1 As shown. Figure 1 It can be seen that the Cu synthesized by hot injection in Example 1 7 S 4 It has a good hexagonal structure, and the size of these hexagonal nanosheets is concentrated between 38-42 nm.
[0024] TEM image of the CdS nanosheets prepared in Example 1, as shown in Figure 2 As shown. Figure 2 It can be seen that the CdS nanosheets prepared by the cation exchange method in Example 1 and the Cu 7 S 4 The nanosheet template has a similar size distribution, but the hexagonal outlines become blurred ( Figure 2 a). From Figure 2 It can be seen from b that the CdS nanosheets belong to the hexagonal wurtzite crystal phase. Combined with the high-resolution TEM image analysis, it can be seen that ( Figure 2 c and d), the upper and lower basal planes of the CdS nanosheet are {002} crystal planes.
[0025] The TEM image of ZnSe obtained in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that the ZnSe prepared by hot injection in Example 1 exhibits irregular morphology, including granular, flower-like and the like.
[0026] TEM image of the CdS-ZnSe heterojunction photocatalyst prepared in Example 1, as shown in Figure 4 As shown. Figure 4 It can be seen that in Example 1, the CdS-ZnSe heterojunction photocatalyst was prepared by the seed growth method combined with the hot injection method, wherein the CdS nanosheets are located in the middle, and the {002} crystal plane of the CdS nanosheets is well exposed. The irregular particles located at the edge of the nanosheets are ZnSe.
[0027] The EDS element distribution diagram of the CdS-ZnSe heterojunction photocatalyst prepared in Example 1 is as follows: Figure 5 As shown. Figure 5 It can be seen that the Zn and Se elements are located at the edges of the nanosheets, while Cd and S are mainly located in the center of the heterojunction.
[0028] Example 2 A method for preparing a CdS-ZnSe photocatalyst with a high exposure ratio of a {002} active crystal plane comprises the following steps: 1. Cu 7 S4 Preparation of nanosheets 1.1 mmol CuCl 2 8 mL of oleylamine were added to a three-necked flask, heated to 110 °C, dehydrated and deoxygenated for 15 min, and then heated to 210 °C and maintained until the solution was clear and light yellow. During this period, 0.55 mmol of NH 4 SCN was dissolved in 2.5 mL of oleylamine. The solution was then injected into a three-necked flask and reacted at 200 °C for 20 min. After the reaction was completed, it was naturally cooled to room temperature and centrifuged at 5500 rpm for 3 minutes.
[0029] 2. Preparation of CdS Nanosheet Seeds 3 mmol of CdO, 6 mL of oleic acid, and 4 mL of 1-octadecene were added to a three-necked flask, heated to 110°C, and dehydrated and deoxygenated for 10 min, then heated to 240°C and maintained until CdO was completely dissolved. 7 S 4 The nanosheets were evenly dispersed in 2 mL of trioctylphosphine solution. The reaction system was then cooled to 190 °C and Cu 7 S 4 The trioctylphosphine solution was injected into the reaction system at this temperature, and then reacted at 170°C for 10 minutes. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000 rpm for 4 minutes.
[0030] 3. Preparation of CdS-ZnSe heterojunction 0.25 mmol of ZnO, 1.2 mL of oleic acid, and 7 mL of 1-octadecene were added to a three-necked flask, heated to 110 °C, dehydrated and deoxygenated for 10 min, and then heated to 300 °C and maintained until ZnO was completely dissolved. During this period, 0.17 mmol of CdS nanosheet seeds and 0.125 mmol of diphenyl diselenide were evenly dispersed in 1.2 mL of oleylamine. The reaction system was then cooled to 255 °C, and the prepared oleylamine solution was injected into the reaction system, then heated to 260 °C for 25 min, cooled to room temperature after the reaction was completed, and centrifuged at 8000 rpm for 4 minutes.
[0031] Example 3 A method for preparing a CdS-ZnSe photocatalyst with a high exposure ratio of a {002} active crystal plane comprises the following steps: 1. Cu 7 S 4 Preparation of nanosheets 0.9 mmol CuCl 28 mL of oleylamine were added to a three-necked flask, heated to 120 °C, dehydrated and deoxygenated for 10 min, and then heated to 210 °C and maintained until the solution was clear and light yellow. During this period, 0.45 mmol of NH 4 SCN was dissolved in 2 mL of oleylamine, and then the above solution was injected into a three-necked flask and reacted at 195°C for 22 minutes. After the reaction was completed, it was naturally cooled to room temperature and centrifuged at 6000 rpm for 3 minutes.
[0032] 2. Preparation of CdS Nanosheet Seeds 2.5 mmol of CdO, 5 mL of oleic acid, and 5 mL of 1-octadecene were added to a three-necked flask, heated to 120°C, and dehydrated and deoxygenated for 10 min, then heated to 240°C and maintained until CdO was completely dissolved. 7 S 4 The nanosheets were evenly dispersed in 2.5 mL of trioctylphosphine solution. The reaction system was then cooled to 185°C and Cu 7 S 4 The trioctylphosphine solution was injected into the reaction system at this temperature, and then reacted at 175°C for 10 minutes. After the reaction was completed, it was cooled to room temperature and centrifuged at 8000 rpm for 5 minutes.
[0033] 3. Preparation of CdS-ZnSe heterojunction 0.22 mmol of ZnO, 1.4 mL of oleic acid, and 7 mL of 1-octadecene were added to a three-necked flask, heated to 120 °C, dehydrated and deoxygenated for 10 min, and then heated to 290 °C and maintained until ZnO was completely dissolved. During this period, 0.2 mmol of CdS nanosheet seeds and 0.11 mmol of diphenyl diselenide were evenly dispersed in 1.4 mL of oleylamine. The reaction system was then cooled to 250 °C, and the prepared oleylamine solution was injected into the reaction system, then heated to 265 °C for 25 min, cooled to room temperature after the reaction was completed, and centrifuged at 8000 rpm for 5 minutes.
[0034] Application example: Photocatalytic water decomposition to produce H 2 Test The CdS, ZnSe, and CdS-ZnSe photocatalysts prepared in Example 1 were subjected to phase transfer treatment, and 10 mg of each was taken and dispersed in 100 mL of 0.5 mol / L Na 2 S and 0.5 mol / L NaSO 3 The suspension was then placed in a 250 mL photoreaction cell to perform photocatalytic water decomposition to produce H2 The reaction was performed by gas chromatography every 1 h for H 2 The output is automatically detected and analyzed. The results are as follows Figure 6 shown.
[0035] Depend on Figure 6 It can be seen that in Example 1, CdS-ZnSe photocatalytic water decomposition to produce H 2 The rate is 17.1 mmol·g -1 ·h -1 , respectively CdS nanosheets (1.9 mmol·g -1 ·h -1 ) is 9 times that of ZnSe nanoparticles (0.06 mmol·g -1 ·h -1 ) is 285 times ( Figure 6 a). After 20 hours of cycling, CdS-ZnSe still maintains good photocatalytic performance ( Figure 6 b). Compared with the reported one-dimensional hyperbranched or rod-shaped CdS@ZnSe heterojunctions, this structure has obvious advantages in photocatalytic hydrogen production applications.
[0036] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane, characterized in that: The following steps are involved: (1) Preparation of Cu7S4 nanosheets: CuCl2 and oleylamine were added to a three-necked flask, dehydrated and deoxygenated, and then heated until the solution was clear and light yellow. NH4SCN oleylamine solution was added and reacted at a certain temperature. After the reaction was completed, the mixture was naturally cooled to room temperature, and the product was separated by centrifugation to obtain Cu7S4 nanosheets. (2) Preparation of CdS nanosheet seed crystals: CdO, oleic acid and 1-octadecene are added to a three-necked flask, dehydrated and deoxygenated, and then heated to react until the solution is clarified to obtain a mixed solution A. During this period, the Cu7S4 nanosheets obtained in step (1) are uniformly dispersed in trioctylphosphine to obtain a trioctylphosphine solution of Cu7S4, and then the mixed solution A is cooled, and the trioctylphosphine solution of Cu7S4 is injected into the mixed solution A, and reacted at a certain temperature. After the reaction is completed, it is cooled to room temperature, and the product is separated by centrifugation to obtain CdS nanosheet seed crystals; (3) Preparation of CdS-ZnSe heterojunction: ZnO, oleic acid and 1-octadecene are added to a three-necked flask, dehydrated and deoxygenated, and then heated to react until the solution is clarified to obtain a mixed solution B. During this period, diphenyl diselenide and the CdS nanosheet seeds obtained in step (2) are uniformly dispersed in oleylamine to obtain an oleylamine solution C. The mixed solution B is then cooled, and the prepared oleylamine solution C is injected into the mixed solution B. The reaction is maintained at a certain temperature. After the reaction is completed, the mixture is cooled to room temperature, and the product is separated by centrifugation to obtain the CdS-ZnSe heterojunction photocatalytic material.
2. The method for preparing the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 1, characterized in that: In step (1), the molar ratio of CuCl2 to NH4SCN is (0.9-1.1):(0.45-0.55), and the volume of oleylamine required to dissolve 0.9-1.1 mmol CuCl2 is 8-10 mL; in the oleylamine solution of NH4SCN, the volume of oleylamine required to dissolve 0.45-0.55 mmol NH4SCN is 2-2.5 mL.
3. The method for preparing the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 1, characterized in that: In step (1), the dehydration and deoxygenation treatment time is 10-15 minutes; the heating temperature is 195-205°C, at which temperature the NH4SCN oleylamine solution is injected, the reaction temperature is 190-195°C, and the reaction time is 20-25 minutes; the centrifugal separation speed is 5000-6000 rpm, and the centrifugation time is 2-3 minutes.
4. The method for preparing the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 1, characterized in that: In step (2), the molar ratio of CdO to Cu7S4 is (2-3):(0.12-0.15). Based on the molar ratio of 2mmol CdO, the required volume of oleic acid is 4-6mL, and the volume of 1-octadecene is 4-6mL; the time for the dehydration and deoxygenation treatment is 10-15min; based on the molar ratio of 0.12-0.15mmol Cu7S4 nanosheets, the required volume of trioctylphosphine is 2-2.5mL.
5. The method for preparing the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 1, characterized in that: In step (2), the heating temperature is 230-240°C, the mixed solution A is cooled to 180-190°C, and the trioctylphosphine solution of Cu7S4 is injected into the mixed solution A at this temperature. The reaction temperature is 160-180°C, and the reaction time is 10-12 min. The centrifugal separation speed is 8000-9000 rpm, and the centrifugation time is 3-5 min.
6. The method for preparing the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 1, characterized in that: In step (3), the molar ratio of the ZnO, CdS nanosheet seeds and diphenyl diselenide is 0.2-0.25mmol:0.15-0.2mmol:0.1-0.125mmol. Based on 0.2-0.25mmol of ZnO, the required volume of oleic acid is 1.2-1.5mL, and the volume of 1-octadecene is 7-8mL; based on 0.15-0.2mmol of CdS nanosheet seeds, the required volume of oleylamine is 1.2-1.5mL.
7. The method for preparing the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 1, characterized in that: In step (3), the dehydration and deoxygenation treatment time is 15-20 minutes; the heating temperature is 280-300°C, the mixed solution B is cooled to 250-260°C, and at this temperature, the oleylamine solution C is injected into the mixed solution B; the reaction temperature is 260-270°C, and the reaction time is 20-25 minutes; the centrifugal separation speed is 8000-9000 rpm, and the centrifugation time is 3-5 minutes.
8. A CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane obtained according to the preparation method of any one of claims 1 to 7.
9. Use of the CdS-ZnSe heterojunction photocatalytic material with a high exposure ratio of the {002} active crystal plane according to claim 8 in photocatalytic water decomposition to produce H2.
10. The use according to claim 9, characterized in that: The photocatalytic water splitting rate of CdS-ZnSe heterojunction to produce H2 is as high as 17.1 mmol·g under the condition of no co-catalyst -1 ·h -1 .